Faktor-faktor yang Berhubungan dengan Kejadian Stunting pada Anak Balita di Puskesmas Alak Kota Kupang Tahun 2022 - Astriana Tualaka; Indriati A.Tedju Hinga; Rut Rosina Riwu (Yayasan Literasi Sains Indonesia, 2023)
Stunting is a condition where there is failure to thrive in children under five caused by chronic malnutrition so that the child is too short for his age. The prevalence of short and very short toddlers aged 0-59 months in Indonesia in 2017 was 9.8% and 19.8%, respectively. This condition increased from the previous year, namely the prevalence of very short toddlers at 8.5% and short toddlers by 9%. The province with the highest prevalence of stunting or stunting aged 0-59 months is East Nusa Tenggara while the lowest province of stunting is Bali. Alak Health Center is a health center that is included in the priority of treatment stunting in Kupang City, NTT. This study aims to determine what factors can affect the incidence of stunting in toddlers in the working area of ​​the Alak Health Center. The type of research used is an analytical survey research with a case-control. The sample size in this study amounted to 188 mothers who have children under five, including 94 toddlers with stunting and 94 toddlers who are not stunted. Analysis of the data used is univariable analysis and bivariable analysis with statistical tests using chi-square. The results showed that the factors related to the incidence of stunting were poor parenting (p-value =0.000), history of infectious diseases (p-value =0.002), and parental income (p-value =0.001) were factors that affect the incidence of stunting in toddlers. Health centers are expected to take advantage of promotional media health in order to increase maternal knowledge about the dangers of stunting and its prevention.